Representasi Perdamaian dalam Film Religi “Mencari Hilal” - Taufik Hidayatullah, Moch.; Budi Lestari, sri (Interaksi Online, 2020)
This research uses a critical paradigm to critically uncover the meanings and ideas contained in the film's text. Using a qualitative approach and John Fiske's semiotic research method based on The Codes of Television, the researcher wanted to find out how the film text of “Mencari Hilal” for peace represented audio and visual aspect in the film. The chosen lexia is analyzed through three levels: the level of reality, representation, and ideology. The researcher applies data collection techniques in the form of observation and documentation to analyze the text in the film “Mencari Hilal”. The theory used is Stuart Hall's representation theory and Johan Galtung's peace theory. The results of this research are that the film “Mencari Hilal” presents a false representation of peace—betraying indicator of sign that refer to the existence of peace itself, namely equality. Peace is described as being inseparable from the influence of the dominant group namely Muslims as the majority religious community. The impact, instead of representing peace, is still inseparable from the influence of the Muslim perspective as the dominant group—which adheres to the dominant ideology—in creating a discourse of peace. Dominant groups carry out dominant ideas in the discourse of peace towards minority religious groups that create various impacts in social discourse.